2020
DOI: 10.21203/rs.3.rs-19836/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide analysis of AP2/ERF Transcription Factors in sugarcane Saccharum spontaneum L. Reveals Functional Divergence During Drought, Salt Stress and Plant Hormones Treatment

Abstract: Background: APETALA2/ETHYLENE RESPONSIVE FACTOR (AP2/ERF) transcription factors play important roles in plant growth, development, metabolism, as well as in biotic and abiotic stress responses. However, there are few studies concerning AP2/ERF genes in sugarcane, which is the most critical sugar and energy crop worldwide. Results: A total of 218 AP2/ERF genes were identified in the Saccharum spontaneum genome. Phylogenetic analysis showed that these genes could be divided into four groups, including 43 AP2s, 1… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
(71 reference statements)
1
0
0
Order By: Relevance
“…We found that in the two kinomes the large majority of segmentally duplicated PKs were under negative selection (Ka/Ks<1), while a smaller percentage were under positive selection (Ka/Ks>1), and very few were under neutral selection (Ka/Ks=1). This pattern is similar to those observed in the soybean, grapevine and pineapple kinomes (Liu et al, 2015;Zhu et al, 2018a, b) and to those reported in smaller gene families in Ssp (Wang et al, 2019c;Li et al, 2020a) and sorghum (Malviya et al, 2016;Anand et al, 2017;Mittal et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…We found that in the two kinomes the large majority of segmentally duplicated PKs were under negative selection (Ka/Ks<1), while a smaller percentage were under positive selection (Ka/Ks>1), and very few were under neutral selection (Ka/Ks=1). This pattern is similar to those observed in the soybean, grapevine and pineapple kinomes (Liu et al, 2015;Zhu et al, 2018a, b) and to those reported in smaller gene families in Ssp (Wang et al, 2019c;Li et al, 2020a) and sorghum (Malviya et al, 2016;Anand et al, 2017;Mittal et al, 2017).…”
Section: Discussionsupporting
confidence: 90%